2021
DOI: 10.1088/1361-6587/ac3499
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear MHD simulation of core plasma collapse events in Wendelstein 7-X

Abstract: Three-dimensional nonlinear MHD simulations study the core collapse events observed in a stellarator experiment, Wendelstein 7-X. In the low magnetic shear configuration like the Wendelstein 7-X, the rotational transform profile is very sensitive to the toroidal current density. The 3D equilibrium with localized toroidal current density is studied. If the toroidal current density follows locally in the middle of the minor radius, the rotational transform is also changed locally. Sometimes, the magnetic topolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several of the main workhorse nonlinear codes have either demonstrated recent nonlinear MHD extensions for stellarators, or are in the process of being extended for such studies [10][11][12]. In addition, the MIPS code has been used extensively for nonlinear MHD studies of stellarators [13]. While the solution of such detailed nonlinear initial value problems cannot be applied to stellarator optimization directly, it can help to inform and direct the development of a nonlinear analytic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the main workhorse nonlinear codes have either demonstrated recent nonlinear MHD extensions for stellarators, or are in the process of being extended for such studies [10][11][12]. In addition, the MIPS code has been used extensively for nonlinear MHD studies of stellarators [13]. While the solution of such detailed nonlinear initial value problems cannot be applied to stellarator optimization directly, it can help to inform and direct the development of a nonlinear analytic approach.…”
Section: Introductionmentioning
confidence: 99%
“…effects [15][16][17], and nonlinear simulations in simplified cylindrical geometry have shown that such internal kink modes can indeed result in core temperature crashes [18]. In contrast, nonlinear MHD simulations in W7-X geometry using rather different ι profiles with mid-radius ECCD have found that the nonlinear coupling of high-n ballooning modes can induce low-n modes to trigger core crashes by stochasticizing the magnetic field [19].…”
Section: Introductionmentioning
confidence: 99%